Powerful Subjects: The Duplicity of Slave Owners in Nineteenth-Century Cuba - Manuel Barcia (International Journal of Cuban Studies, 2015)
This article explores the ways in which Cuban-based merchants and planters attempted to keep a robust control upon their increasingly large slave population, while endeavouring to show to the rest of the world an idyllic picture of Cuban slavery. By using James C. Scott's concepts of ‘Hidden’ and ‘Public Transcripts’, the article examines primary sources produced precisely by those merchants and planters, sources that were meant to be kept between them. Thus, the article offers a window into their world and a good tool to understand their reasoning.